2011
DOI: 10.1021/ol202046y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Intermolecular Hetero-Dehydro-Diels–Alder Cycloadditions: Regio- and Diasteroselective Synthesis of 5,6-Dihydropyridin-2-ones

Abstract: A novel catalyzed intermolecular hetero-dehydro-Diels-Alder reaction between push-pull 1,3-dien-5-ynes and aldimines or silylaldimines is reported. The sequence is promoted both by gold(I) or silver(I) catalysts and leads to the diastereo-and regioselective formation of 5,6-dihydropyridin-2-ones.The field of metal-catalysis (together with bio-, and organo-catalysis, one of the three feet of the vital catalytic tripod in the current scenario of organic synthesis) has achieved considerable improvement over the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Fernµndez-García et al reported an ovel gold-catalyzed intermolecular [4+ +2] cycloaddition between dienynes and aldimines or silylaldimines (Scheme 14). [17] This aza-DDAr eaction provided diastereo-a nd regioselective accesst o5 ,6-dihydropyridin-2-ones.I nterestingly,t he methoxysubstituted alkynyl carbon behaved in this case as am asked carbonyls urrogate. The electronic nature of the conjugated system (a push-pull system)i sc rucial to the successo ft his intermolecular DDA reaction.…”
Section: Enyne-ene and Enyne-yne Cycloaddition(types II And Iii)mentioning
confidence: 93%
“…Fernµndez-García et al reported an ovel gold-catalyzed intermolecular [4+ +2] cycloaddition between dienynes and aldimines or silylaldimines (Scheme 14). [17] This aza-DDAr eaction provided diastereo-a nd regioselective accesst o5 ,6-dihydropyridin-2-ones.I nterestingly,t he methoxysubstituted alkynyl carbon behaved in this case as am asked carbonyls urrogate. The electronic nature of the conjugated system (a push-pull system)i sc rucial to the successo ft his intermolecular DDA reaction.…”
Section: Enyne-ene and Enyne-yne Cycloaddition(types II And Iii)mentioning
confidence: 93%
“…In conclusion, prior to this study there were very few examples of gold‐catalyzed intermolecular reactions of alkynes with alkenes 1. 4, 5 This study describes gold‐catalyzed [4+2] cycloadditions of 1‐amino‐2‐aryl‐1‐ynes with alkenes 15. The reaction has a wide scope and can accommodate various alkenes, as well as ynamides which are substituted with different aryl groups.…”
Section: Methodsmentioning
confidence: 99%
“…211 On one hand, N-substituted 5,6-dihydropyridin-2-ones are synthesized in moderate yields and in a regio-and diastereoselective manner by mixing push-pull 1,3-dien-5-ynes with aldimines under the same reaction conditions employed in their reaction with nitriles (Scheme 106, eq. 1).…”
Section: Scheme 105 Gold-catalyzed Intermolecular Hetero-dehydro-diementioning
confidence: 99%